Natural Compounds in Hepatic Protection and Injury: A Dual-Spectrum Review of Medicinal Plants - Dilsar Gohil; Rajesh Maheshwari (Pharmacognosy Research, 2026)
Hepatotoxicity remains a persistent global clinical challenge, driven by exposure to a broad spectrum of xenobiotics prescription drugs, over-the-counter medications, industrial chemicals, and increasingly, herbal supplements that disrupt the intricate balance of hepatic homeostasis. Paradoxically, a growing body of evidence demonstrates that many of these same medicinal plants exhibit dose-dependent hepatoprotective activities, highlighting the critical importance of delineating their dual-spectrum effects. In this review, we systematically classify a selection of widely used species into hepatotoxic and hepatoprotective cohorts, detailing their principal bioactive phytochemicals (e.g., pyrrolizidine alkaloids, flavonoids, triterpenoids), key molecular targets (including Nrf2/ARE, NF-κB, caspase cascades, and major CYP450 isoforms), and dose-response safety margins. We further summarize contemporary extraction and standardization methodologies such as supercritical fluid extraction, green solvent systems, and HPLC fingerprinting that ensure reproducibility and quality control across studies. Advanced in vitro and in vivo platforms, including three-dimensional hepatic spheroids and microfluidic liver-on-chip models, are reviewed for their enhanced physiological relevance and predictive capacity. Integration of preclinical data with findings from clinical trials investigating compounds like silymarin, glycyrrhizin, and EGCG is critically examined, with special attention to safety considerations such as herb drug interactions, cumulative toxicity thresholds, and idiosyncratic reactions. Finally, we propose future research trajectories leveraging network pharmacology, nanocarrier delivery systems, and international regulatory harmonization to accelerate the safe translation of phytochemical-based interventions for liver protection.
Keywords: CYP450; Hepatoprotection; Hepatotoxicity; Nrf2; Phytochemicals; Systems Pharmacology.